Pengaruh Penggunaan Media Papan Piktogram Terhadap Minat Dan Hasil Belajar Pada Mata Pelajaran Matematika Siswa Kelas 4 Sekolah Dasar Negeri 1 Rejotangan Kabupaten Tulungagung - Ririn Fatmawati; Ria Fajrin Rizqy Ana (Universitas Pakuan, 2026)
THE EFFECT OF USING PICTOGRAM BOARD MEDIA ON THE INTEREST AND LEARNING OUTCOMES IN THE MATHEMATICS SUBJECT OF GRADE 4 STUDENTS OF STATE ELEMENTARY SCHOOL 1 REJOTANGAN, TULUNGAGUNG DISTRICT This study was motivated by the low level of students’ learning interest and mathematics learning outcomes among fourth-grade students at SD Negeri 1 Rejotangan, Tulungagung Regency. Students tended to be less active, less focused, and experienced difficulties in understanding pictogram material. Therefore, an instructional medium that could help students understand concepts more concretely and attractively was needed. This study aimed to determine the effect of pictogram board media on students’ interest in learning mathematics, mathematics learning outcomes, and both learning interest and learning outcomes simultaneously. This study employed a quantitative approach using a Pre-Experimental Design with a One-Group Pretest–Posttest Design. The research was conducted from May 9 to May 12, 2026, at SD Negeri 1 Rejotangan, Tulungagung Regency, involving 22 fourth-grade students as the research subjects. Data were collected through tests, questionnaires, and documentation. The data were analyzed using Multivariate Analysis of Variance (MANOVA). The results showed that the use of pictogram board media had a significant effect on students’ interest in learning mathematics, with a significance value of 0.001. The use of pictogram board media also had a significant effect on students’ mathematics learning outcomes, with a significance value of 0.001. Furthermore, the multivariate test results indicated significance values of 0.001 for Pillai’s Trace, Wilks’ Lambda, Hotelling’s Trace, and Roy’s Largest Root, demonstrating that the use of pictogram board media had a significant simultaneous effect on students’ learning interest and mathematics learning outcomes. Therefore, pictogram board media can be used as an effective instructional medium to improve the learning interest and mathematics learning outcomes of fourth-grade elementary school students.